The Effect of Using e-module Model Problem Based Learning (PBL) Based on Wetland Environment on Critical Thinking Skills and Environmental Care Attitudes - Mohamad Nor Aufa; Rusmansyah Rusmansyah; Muhammad Hasbie; Akhmad Jaidie; Amalia Yunita (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to analyze the effect of using an E-module with a wetland environment-based PBL model on students' critical thinking skills and environmental care attitudes. This study was a quasi-experimental study with a non-equivalent posttest only control group design. The study population was 150 students, while the sample was selected by random sampling. The number of samples in this study was 64 students who were divided into two classes. The instrument used was a test, namely a question of critical thinking skills in the form of an essay and a non-test in the form of a questionnaire for environmental care attitudes. The collected data were analyzed by using Multivariate Analysis of Variance. The results showed that the significance of the three hypotheses was 0.000, which means less than 0.05 (0,000 <0.05). So, it can be concluded that there is a positive effect of using the E-module with the PBL model on critical thinking skills and environmental care attitudes. The novelty of this study integrates the wetland environment in the learning process using teaching materials in the form of E-modules in the learning process of the topic of acid-base solutions on critical thinking skills and environmental care attitudes of students